'A highly successful model'? The rail franchising business in Britain. Issue 6 (18th August 2017) - Jupe, Robert; Funnell, Warwick
Abstract: A crucial feature of rail privatisation in Britain was franchising. Passenger services were franchised in competitive bidding processes to train operators which were meant to function with declining subsidy. The article adopts the framework of social cost-benefit analysis to examine rail privatisation's impact on three key groups; consumers, producers and the government. It establishes that privatisation did not achieve all the supposed benefits. Further, franchising only appears to be profitable through the use of calculative accounting practices, whereby franchised train operators are portrayed as discrete business entities, whereas they are supported by very substantial, ongoing direct and indirect government subsidies.